Telehealth as a Means of Enabling Health Equity - Kuziemsky, Craig; Hunter, Inga; Udayasankaran, Jai Ganesh; Ranatunga, Prasad; Kulatunga, Gumindu; John, Sheila; John, Oommen; Flórez-Arango, José F.; Ito, Marcia; Ho, Kendall; Gogia, Shahi B.; Araujo, Kleber; Rajput, Vije Kumar; Meijer, Wouter J.; Basu, Arindam (Yearbook of Medical Informatics, 2022)
Objective: The goal of this paper is to provide a consensus review on telehealth delivery prior to and during the COVID-19 pandemic to develop a set of recommendations for designing telehealth services and tools that contribute to system resilience and equitable health.Methods: The IMIA-Telehealth Working Group (WG) members conducted a two-step approach to understand the role of telehealth in enabling global health equity. We first conducted a consensus review on the topic followed by a modified Delphi process to respond to four questions related to the role telehealth can play in developing a resilient and equitable health system.Results: Fifteen WG members from eight countries participated in the Delphi process to share their views. The experts agreed that while telehealth services before and during COVID-19 pandemic have enhanced the delivery of and access to healthcare services, they were also concerned that global telehealth delivery has not been equal for everyone. The group came to a consensus that health system concepts including technology, financing, access to medical supplies and equipment, and governance capacity can all impact the delivery of telehealth services.Conclusion: Telehealth played a significant role in delivering healthcare services during the pandemic. However, telehealth delivery has also led to unintended consequences (UICs) including inequity issues and an increase in the digital divide. Telehealth practitioners, professionals and system designers therefore need to purposely design for equity as part of achieving broader health system goals.
Keywords: Telehealth; equity; resilience; health systems; unintended consequences